2007
DOI: 10.1159/000098041
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine and Preservation of Sound Tooth Structure in Older Adults

Abstract: The Trial to Enhance Elderly Teeth Health (TEETH) was designed to test the impact of regular rinsing with a 0.12% chlorhexidine (CHX) solution on tooth loss, and the causes of tooth loss (caries, periodontal disease and trauma) were also investigated. This paper reports on the effectiveness of a 0.12% CHX solution for controlling caries using a tooth surface (coronal and root) survival analysis. A total of 1,101 low income elders in Seattle (United States) and Vancouver (Canada), aged 60–75 years, were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Analyses could not be performed for varnish containing 22,500 ppm F -(Duraphat), since these studies used Duraphat as a control group without having a second (negative) control group (Ravald and Birkhed 1992;Fure and Lingstrom 2009) or the results were presented according to different indices (DMFRS or texture) and did not report all information required for recalculation (Schaeken et al 1991;Tan et al 2010). For CHX mouth rinses (Powell et al 1999;Wyatt and MacEntee 2004;Wyatt et al 2007) and ozone treatment (Holmes 2003;Baysan and Lynch 2007), recalculation was not possible owing to insufficient data presentation. Thus, meta-analyses were performed only for dentifrice containing 5,000 ppm F -or 1.5% arginine plus 1,450 ppm F -, rinse containing 0.05% to 0.2% NaF (225 to 900 ppm F -), varnish containing SDF or CHX and combined use of dentifrice (1,500 ppm F -), and a rinse containing AmF/SnF 2 (250 ppm F -).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses could not be performed for varnish containing 22,500 ppm F -(Duraphat), since these studies used Duraphat as a control group without having a second (negative) control group (Ravald and Birkhed 1992;Fure and Lingstrom 2009) or the results were presented according to different indices (DMFRS or texture) and did not report all information required for recalculation (Schaeken et al 1991;Tan et al 2010). For CHX mouth rinses (Powell et al 1999;Wyatt and MacEntee 2004;Wyatt et al 2007) and ozone treatment (Holmes 2003;Baysan and Lynch 2007), recalculation was not possible owing to insufficient data presentation. Thus, meta-analyses were performed only for dentifrice containing 5,000 ppm F -or 1.5% arginine plus 1,450 ppm F -, rinse containing 0.05% to 0.2% NaF (225 to 900 ppm F -), varnish containing SDF or CHX and combined use of dentifrice (1,500 ppm F -), and a rinse containing AmF/SnF 2 (250 ppm F -).…”
Section: Resultsmentioning
confidence: 99%
“…The investigators concluded that the daily rinse with 0.25% NaF solution was significantly better than with 0.12% chlorhexidine rinse. A double-blind clinical trial by Wyatt and others 12 also tested the impact of regular rinsing with a 0.12% chlorhexidine solution on caries in low-income elders in Seattle, WA, USA and Vancouver, Canada. The subjects alternated between daily rinsing for one month, followed by weekly rinsing for five months.…”
Section: Mouthrinsesmentioning
confidence: 99%
“…Wyatt et al 21 tested the impact of regularly chewing a solution of chlorhexidine 0.12% among 550 elderly persons. All dental and crown surfaces were monitored for five years.…”
Section: Root Cariesmentioning
confidence: 99%